Simulating Behaviour of Unreinforced and Reinforced Masonry Wall Panels Under Monotonic Lateral Loading - Kasula, Anil; Shakya, Manjip; Karanjit, Sudip; Prajapati, Amit (Journal of Science and Engineering, 2024)
Unreinforced Masonry (URM) structures are extremely vulnerable to seismic activities. Under seismic loads, the failure of these structures is either due to in-plane failure or an out-of-plane failure mechanism. Different seismic retrofitting and strengthening strategies for masonry structures have been developed and implemented in recent decades. The performance of existing URM structures can be greatly improved by retrofitting. This paper uses steel strips with anchor bolt arrangement as reinforcing material for retrofitting purposes. A comparative study of change in lateral load carrying capacity of unreinforced and reinforced masonry wall panels under in-plane lateral load based on numerical simulation is presented in this study. Initially, a 3D numerical model of the URM wall panel is prepared in ABAQUS FEM using Simplified Micro Modelling (SMM) technique. The Concrete Damage Plasticity (CDP) model is used as a material model and the surface-based coupled cohesion-friction model as the interface material. The response of the URM wall panel under displacement-controlled monotonic lateral load is evaluated and validated against experimental results. Another separate numerical model of reinforced masonry is prepared with identical mechanical properties. A comprehensive study is conducted on the change in the performance of both wall panels. The study found that the ultimate load-carrying capacity of reinforced masonry wall panels is increased by 22% compared to the unreinforced masonry wall panel.